Psychological and Intuition Requirements for more attractive Electronic Health Records - Mota, Andhora Silveira Santos; Moura, José Antão Beltrão; Santos, Adriano Araújo; Vieira, Vanissa Wanick (Journal of Health Informatics, 2021)
Objective: To report on an investigation of requirements, with focus on Psychological and Intuition Requirements (PIRs), to make adoption of Electronic Health Records (EHRs) more encompassing and expeditious. Methods: The investigation collected EHR features from the literature, commercially available EHR software and proposed EHR standards. By using a mix of a modified Delphi method, a questionnaire-based survey, and interviews with EHR developers and usage stakeholders, the investigation: 1) classified requirements of EHRs; 2) ranked resulting classes by their importance for EHR adoption; and, 3) analysed whether PIRs were in the most important classes. Results: Ten EHR requirements classes were elicited and had different concentrations of PIRs. PIRs were proven useful for EHR adoption, but standards should be also reinforced. Functional requirements had smaller importance. Conclusion: PIRs from security and ease of use classes should have higher priority in EHR development, maintenance, and evolution to ease adoption.